(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Nature remains one of the focal inspirational issues in Rabindranath Tagore’s creative journey. Being the nature lover, nature plays a pivotal role in almost all of his literary works especially in his poems and songs. Although the central themes of Tagore’s short stories always occupy the household matters of rural people viz., controversies among family members regarding property, various individual struggles as well as the societal problems especially of rural areas of Bengal humorous, scientific thoughts, characters in urban settings, supernatural and fantasy themes and many more, still nature runs consistently in his stories side by side. In his short stories very often nature remains as the background of the story as a soul mate, a true companion of loneliness, etc. Along with the central themes of the stories, Tagore’s concentration remains to draw the natural sceneries of the surroundings. So, in this write up attempt has been made to find out how Tagore’s short stories reflects nature as well as what are the main concerns of Tagore to represent nature in various ways. In the stories of Tagore nature is represented in the form of river, trees, flowers, cows, birds, hills, sun, moon, etc. He realised the presence of divinity in all these things and considered to have worth of existence. He considers him as a member among all these things as well as realised the intuitive and spiritual bond between him and nature. In the short stories nature plays the role of a friend, philosopher and guide to mankind. It is also remains the source of joy, peace and tranquility of mind.